Degradation of Semiconductor Manufacturing Wastewater by Using a Novel Magnetic Composite TiO2/Fe3O4 Photoreactor Design. (14th June 2012) - Chang, Chen-Yu; Hsieh, Yung-Hsu
Abstract : The purpose of this research is to develop a photocatalytic TiO2 that can be activated by visible light and can be conveniently recollected for reusing. This research synthesizes the 20 to 40 nm TiO2 /Fe3 O4 particles with magnetization of 5.8 emu/g using the modified sol-gel method followed by 500°C calcinations. The experiment verified that visible fluorescent light (VFL, contains no UV-A) could activate the photocatalytic activity of TiO2 /Fe3 O4 particles as did ultraviolet A light (UV-A, 360 nm). Regular magnets can be used to separate TiO2 /Fe3 O4 particles from solution. The results indicate that VFL-sirradiated TiO2 /Fe3 O4 particles could decompose isopropanol (IPA) in the absence of UV-A and the issue of TiO2 /Fe3 O4 recollection from water for reusing is also resolved.